2020
DOI: 10.3390/ma13081873
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Cu3N/MoS2 Heterojunction through Magnetron Sputtering and Investigation of Its Structure and Optical Performance

Abstract: Cu3N/MoS2 heterojunction was prepared through magnetron sputtering, and its optical band gap was investigated. Results showed that the prepared Cu3N/MoS2 heterojunction had a clear surface heterojunction structure, uniform surface grains, and no evident cracks. The optical band gap (1.98 eV) of Cu3N/MoS2 heterojunction was obtained by analyzing the ultraviolet-visible transmission spectrum. The valence and conduction band offsets of Cu3N/MoS2 heterojunction were 1.42 and 0.82 eV, respectively. The Cu3N film an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In addition, thanks to its good electrical properties and the ease with which it can be fabricated, the use of this material as a solar absorber could help avoid the hightemperature steps involved in the fabrication of solar-grade silicon. Furthermore, thanks to bipolar doping [17], this material can be profitably used in rectifying heterojunctions [18][19][20] as well as homojunctions [8][9][10][11][12][13][14][15][16][17][18][19][20][21], and in solar cells [8,17,22].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, thanks to its good electrical properties and the ease with which it can be fabricated, the use of this material as a solar absorber could help avoid the hightemperature steps involved in the fabrication of solar-grade silicon. Furthermore, thanks to bipolar doping [17], this material can be profitably used in rectifying heterojunctions [18][19][20] as well as homojunctions [8][9][10][11][12][13][14][15][16][17][18][19][20][21], and in solar cells [8,17,22].…”
Section: Introductionmentioning
confidence: 99%
“…Liwen et al reported a Cu 3 N/MoS 2 heterostructure with a clear surface without any cracks and uniform grains at the surface. 35 A type-II heterojunction is formed between a layer of Cu 3 N and multilayer MoS 2 . After the formation of the heterojunction, the electrons move from the interface of MoS 2 to Cu 3 N because of a higher Fermi level of Cu 3 N than the MoS 2 .…”
Section: Growth and Integration Of Heterostructuresmentioning
confidence: 99%
“…It is very necessary to study the optical properties of heterojunction, because optical properties play an important role in photoelectric detection equipment and electronic equipment [39,40]. It is proved that the heterojunction formed by coupling two different semiconductor materials will improve the optical properties of semiconductor materials [41,42]. Therefore, we studied and compared the optical properties of ZnO/WSe 2 heterostructures before and after vacancy generation, including dielectric function and optical absorption coefficient, as shown in Figure 7.…”
Section: Optical Propertiesmentioning
confidence: 99%